PENATAAN KAMPUNG TUA TANJUNG RIAU MENJADI KAMPUNG BUDAYA DAN KAMPUNG CYBER SEBAGAI DESTINASI WISATA UNGGULAN - Yayat Yatna Suhara; Abdul rohim; Yuanita FD Sidabutar (Universitas Batam, 2023)
Cultural tourism is one of the areas of tourism that is in great demand in Indonesia, apart from that the cultural tourism market has a huge opportunity to continue to be developed. One type of cultural tourism is cultural tourism. Unfortunately, people's interest in culture is not high enough, so awareness of the importance of indigenous culture is reduced. One of them is indicated by the level of loss of original culture. In fact, culture is a reflection of the culture and life of a nation in the past which then becomes learning material for life in the present and in the future. Culture or culture is aimed at enhancing human dignity, national identity and personality, strengthening national pride and self-respect and strengthening the spirit of national unity and integrity as a reflection of cultured development that upholds human values. The potential of local culture and wisdom in tourism development is part of the product of human creativity that has economic value. The aim of this research is to analyze culture-based tourism and Cyber Village in Kampung Tua Tanjung Riau as a Leading Tourist Destination.